Use of Viscoplastic Damper for Improving the Resistance of Steel Frames to Blast Loading - Abdollahzadeh, Gholamreza; Faghihmaleki, Hadi; Jamnani, Hamed Hamidi; Bardar, Atefeh Ebrahimi (UI Scholars Hub, 2020)
In this paper, we evaluated the effect of viscoplastic dampers on the response of steel frames under blast loading. We used SAP2000 software and link elements to investigate the responses of nine-story steel frames with and without dampers. The proposed viscoplastic damper is a new type of viscous damper. The application of this damper is based on the availability of its constituent materials. The damper acts as a viscoelastic damper at low levels of vibration, but it acts as a combination of viscoelastic operator and metal-yielding device at extreme levels of vibration. With respect to the height of the structure, the need for the correct distribution is underlined, which is addressed by developing a non-uniform loading at the height of the structure. We used A.T.-Blast software program to measure the required parameters to calculate the pressure coming from the blast. The comparison of the simulation results with and without dampers demonstrated about 33% reduction in responses with respect to the top floor displacements and about 59% reduction in modeling the nine-story steel frame with brass and bending moments at column bases, which represents the optimal operation of viscoplastic damper in steel frame under blast loading. It is demonstrated that using viscoplastic damper with brace improves the blast resistance of structures.